2008
DOI: 10.1007/s10741-008-9112-z
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea: the new cardiovascular disease. Part I: obstructive sleep apnea and the pathogenesis of vascular disease

Abstract: Obstructive sleep apnea (OSA) is increasingly recognized as a novel cardiovascular risk factor. OSA is implicated in the pathogenesis of hypertension, left ventricular dysfunction, coronary artery disease and stroke. OSA exerts its negative cardiovascular consequences through its unique pattern of intermittent hypoxia. Endothelial dysfunction, oxidative stress, and inflammation are all consequences of OSA directly linked to intermittent hypoxia and critical pathways in the pathogenesis of cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 145 publications
1
49
0
1
Order By: Relevance
“…P > .05 Kruskal Wallis, P < .05. b According to the age parameter there was a significant relationship between with and without CVD in the AHI !30 patients. atherosclerosis, and other cardiovascular outcomes via increasing the inflammation 52,[59][60][61]. Many studies have shown that increased RDW values are also related to adverse outcomes in cardiovascular as well as non-CVDs including peripheral artery disease, unstable angina, HT, heart failure, acute dyspnea, cardiovascular, and thrombotic disorders.…”
mentioning
confidence: 99%
“…P > .05 Kruskal Wallis, P < .05. b According to the age parameter there was a significant relationship between with and without CVD in the AHI !30 patients. atherosclerosis, and other cardiovascular outcomes via increasing the inflammation 52,[59][60][61]. Many studies have shown that increased RDW values are also related to adverse outcomes in cardiovascular as well as non-CVDs including peripheral artery disease, unstable angina, HT, heart failure, acute dyspnea, cardiovascular, and thrombotic disorders.…”
mentioning
confidence: 99%
“…With reperfusion, these reactions proceed with a sudden increase in ROS, which overwhelms usual cellular antioxidant defenses, leading to uncontrolled oxidation of vital cellular biomolecules (56). Experimental data support this hypothesis, and an expanding body of research suggests that it may apply to patients with sleep apnea as well (56,6163). …”
Section: Pathophysiologic Consequencesmentioning
confidence: 84%
“…Most recent studies in animal models of CIH as well as in OSA patients confirm that OSA is associated with oxidative stress, which generally correlates with the severity of sleep apnea. 16,23 CIH-provoked mild and transient oxidative stress can induce adaptation, but severe and persistent CIH may provoke maladaptation as in OSA patients if untreated. As oxidative imbalance has been accepted as a trigger for cardiac dysfunction, the early detection of increased oxidative stress in OSA patients is of importance for risk stratification and strict control regarding CPAP compliance and treatment.…”
Section: Discussionmentioning
confidence: 99%